Epicardial adipose tissue and atrial fibrillation: guilty as charged or guilty by association?. (25th November 2020) - Sousa, J; Matos, D; Ferreira, A; Abecasis, J; Saraiva, C; Freitas, P; Carmo, J; Carvalho, S; Rodrigues, G; Durazzo, A; Costa, F.M; Carmo, P; et al.
Abstract: Background: Epicardial adipose tissue (EAT) has been linked to the presence and burden of atrial fibrillation (AF). However, it is still unclear whether this relationship is causal or simply a surrogate marker of other risk factors commonly associated with AF. Purpose: The purpose of this study was to assess the relationship between these factors and EAT, and to compare their performance in predicting AF recurrence after an ablation procedure. Methods: We assessed 575 consecutive patients (mean age 61±11 years, 62% male) undergoing AF ablation preceded by cardiac CT in a high-volume ablation center. EAT was measured on cardiac CT using a modified simplified method. Patients were divided into 2 groups (above vs. below the median EAT volume). Cox regression was used to assess the relationship between epicardial fat, risk factors, and AF relapse. Results: Patients with above-median EAT volume were older (p<0.001), more often male (OR 1.7, p=0.002), had higher body mass index, and higher prevalence of smoking, hypertension, diabetes and dyslipidemia (p<0.05). Non-paroxysmal AF was also more common in those with above-median EAT volume. During a median follow-up of 18 months, 232 patients (40.3%) suffered AF recurrence. After adjustment for BMI and other univariate predictors of relapse, three variables emerged independently associated with time to AF recurrence: non-paroxysmal AF (HR 2.1, 95% CI: 1.5–2.7, p<0.001), indexed left atrial (LA) volume (HR 1.006 per mL/m 2, 95% CI: 1.002–1.011, p<0.001), and indexed epicardial fat volume (HR 1.87 per mL/m 2, 95% CI: 1.66–2.1, p<0.001). None of the classic cardiovascular risk factors were an independent predictor of AF recurrence (all p>0.10). Conclusion: Classic cardiovascular risk factors are more prevalent in patients with higher amounts of epicardial fat. However, unlike these risk factors, EAT is a powerful predictor of AF recurrence after ablation. These findings suggest that EAT is not merely a surrogate marker, but an important participant in the pathophysiology of AF. Funding Acknowledgement: Type of funding source: None